2019
DOI: 10.1051/itmconf/20192902008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical testing of steel beam-to-column bolted extended end-plate connection with haunches

Abstract: During the European research project entitled EQUALJOINTS (European pre-Qualified steel JOINTS) [1], which recently concluded, the matter of providing a set of pre-qualification procedures for moment resisting beam-to-column connections which are currently used in Europe has been addressed. During the experimental campaign 24 specimens with bolted extended end-plate connections with haunches were tested. The current paper presents the numerical model which has been developed such that numerical testing may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…As suggested by Ruffley (2011) [46], 3D solid elements were used to simulate the finite element models. As shown in Figure 7, C3D8R [47] (first order reduced integration continuous element), a six-edge solid element type that allows nonlinear geometric and material behavior, is used in all models [12,21]. Based on a study carried out for the finite element mesh sensitivity, the size of mesh for different elements determined as 10mm for endplate and column stiffeners, 5mm for bolts, 20mm for beam and haunch, 15mm for beam stiffeners, 10mm for column panel zone area, and an approximate mesh size of 100mm for places far from the connection.…”
Section: Element Type and Mesh Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested by Ruffley (2011) [46], 3D solid elements were used to simulate the finite element models. As shown in Figure 7, C3D8R [47] (first order reduced integration continuous element), a six-edge solid element type that allows nonlinear geometric and material behavior, is used in all models [12,21]. Based on a study carried out for the finite element mesh sensitivity, the size of mesh for different elements determined as 10mm for endplate and column stiffeners, 5mm for bolts, 20mm for beam and haunch, 15mm for beam stiffeners, 10mm for column panel zone area, and an approximate mesh size of 100mm for places far from the connection.…”
Section: Element Type and Mesh Sensitivitymentioning
confidence: 99%
“…Several studies have been carried out on the reinforcement of moment resisting connection before the Northridge earthquake. The studies indicated that the plastic hinge formed in the beam with the effect of the haunch on the lower flange of the beam and it was suitable for earthquake resistant structure design [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same problem can be highlighted in the connections of replaceable links, where the bolts undergo large deformations (Figure 1b). In the literature there are some models that can be used to reproduce the stripping of the nut for HV bolts or shank fracture for HR bolts [9][10][11][12][13][14], but a model capable of fully capturing the behaviour of HV bolts under combined tension and bending is missing [4].…”
Section: Introductionmentioning
confidence: 99%
“…The same problem can be highlighted in the connections of replaceable links, where the bolts undergo large deformations (Figure 1b). In the literature there are some models that can be used to reproduce the stripping of the nut for HV bolts or shank fracture for HR bolts [9][10][11][12][13][14], but a model capable of fully capturing the behaviour of HV bolts under combined tension and bending is missing [4]. Much research [4][5][6][7][8][9][10][11][12][13][14][15][16][17] was accomplished in recent years to develop models able to replicate, with a good level of accuracy, the damage and failure of bolts subjected to a specific action such as pure tension or shear [9][10][11][12][13][14], but most of them require the computation of the parameters needed to implement the failure mechanism of the materials and of the joints themselves.…”
Section: Introductionmentioning
confidence: 99%